Digital approaches to the aesthetic and stylistic design of rural streets - Chenxi, Li; Bulhakova, T. (Art and Design, 2025)
Rural revitalisation is a growing global priority aimed at countering urban-rural imbalances, preserving cultural heritage, and improving the quality of rural life. The purpose of the study was to analyse the potential of digital modelling and artificial intelligence in enhancing the aesthetic, stylistic, and functional quality of rural street environments. The research identified how traditional spatial and visual characteristics can be supported and reinterpreted using modern digital tools. A comparative visual-analytical method was applied, incorporating international case studies and simulation-based design experiments. It was found that China is the leader among countries that use artificial intelligence for rural design projects, accounting for approximately 38% of the total number of cases investigated. Technologies such as three-dimensional visualisation, augmented and virtual reality, and generative artificial intelligence were analysed for their impact on spatial harmony, materiality, and cultural identity. Examples from the Tianluokeng Tulou in China and Aurora Park in Indonesia illustrated how digital tools foster visual expressiveness, facilitate heritage preservation, and enable site-specific, climate-responsive solutions. Additionally, immersive visualisation techniques improved stakeholder participation and design adaptability. The study introduced an integrated approach combining digital innovation with vernacular aesthetics, showing that AI-assisted tools contribute to both artistic expression and functional optimisation. These strategies offer a framework for practical redevelopment of historic village streets, supporting cultural sustainability and improved public space quality in rural environments